Assessment of nitrate transport in the unsaturated (coarse gravel) zone by means of tracing experiment (Selniška dobrava, Slovenia) - Anja Koroša (Geologija, 2015)
Nitrate pollution in groundwater, originating mainly from agricultural activities, remains a worldwide issue. This is also pertinent to Slovenia, where nitrate leaching from agricultural areas is one of the major groundwater resource management problems. The contamination spread in the aquifer is directly related to the hydraulic properties of the upper, unsaturated and the lower, saturated zone. The article presents study of water and nitrate pollution transport in the unsaturated zone in a fild laboratory – lysimeter in Selniška dobrava. Water and nitrate transport parameters were estimated by a combined tracing experiment with deuterated water and Ca(NO3)2. Deuterium was used as a conservative tracer of water movement, and Ca(NO3)2 was used as a nitrate tracer in the unsaturated zone. The δ2H and nitrate concentrations in the unsaturated zone water were measured monthly during the period from April 2006 to July 2007. All together 36 samplings were performed. The fastest and dominant flw velocities were calculated based on injection time, the fist tracer appearance time, and the time of highest concentration. Mean flw velocity and vertical dispersion were estimated by an analytical best-fi method using the one-dimensional convection–dispersion model. The results were used to estimate the nitrate transport parameters in the coarse gravel aquifer Selniška dobrava. They can be used also for nitrate transport estimations in other aquifers with similar hydrogeological characteristics and can serve as a base for determining the measures for nitrate reduction in groundwater.